1998
DOI: 10.1037/h0088978
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of treatment integrity in school-based behavioral consultation.

Abstract: In regular education settings, 29 consultant-consultee dyads completed traditional problem identification and problem analysis interviews according to Bergan's (1977) behavioral consultation model. Independent variables assessed included severity of the child's problem behavior, treatment acceptability, and verbal interaction style. Verbal interactions were manipulated to measure the effects of "collaborative" versus "prescriptive" consultation conditions. The relationships among independent variables and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 32 publications
8
105
0
1
Order By: Relevance
“…Community Partners indicated that they were adhering to all program components, but the research team observed wide variability in adherence across the steps of the program (from 46% to 83%). This type of discrepancy is consistent with other research using teachers as interventionists (Resnicow et al, 1998;Wickstrom, Jones, LaFleur, & Witt, 1998). Clearly, the Community Partners' self-assessments were not consistent with observer ratings, and the students did not appear to be receiving the complete intervention on a consistent basis.…”
Section: Literacy Development Programsupporting
confidence: 84%
“…Community Partners indicated that they were adhering to all program components, but the research team observed wide variability in adherence across the steps of the program (from 46% to 83%). This type of discrepancy is consistent with other research using teachers as interventionists (Resnicow et al, 1998;Wickstrom, Jones, LaFleur, & Witt, 1998). Clearly, the Community Partners' self-assessments were not consistent with observer ratings, and the students did not appear to be receiving the complete intervention on a consistent basis.…”
Section: Literacy Development Programsupporting
confidence: 84%
“…For example, teachers' attitudes about the acceptability of the proposed intervention, or the degree to which an individual perceives a treatment procedure as fair, reasonable, appropriate, and unintrusive (Kazdin, 1980), have been hypothesized to affect treatment integrity . In contrast, Wickstrom et al (1998) and Noell et al (2005) found acceptability to be unrelated to reported integrity levels. Noell et al also showed teacher acceptability to be unrelated to student outcome, indicating that some teachers found an intervention acceptable even though the student's behavior did not improve.…”
Section: Uncontrollable Consultation Characteristicsmentioning
confidence: 86%
“…Some researchers have debated whether consultants who work in collaboration with teachers produce more significant behavior change in the teacher than consultants who dictate intervention approaches without collaborating with teachers (e.g., Sheridan, 1992;Witt, 1990). Wickstrom, Jones, LaFleur, and Witt (1998) found the treatment integrity of interventions to be unaffected by the consultation approach used; integrity dropped quickly following training on the intervention across all teachers, regardless of whether a consultant collaborated with or prescribed an intervention to them. In fact, Noell (2007) suggested that a collaborative, co-investigator approach in consultation may even threaten treatment integrity by placing more emphasis on changing the behavior of the child rather than that of the teacher.…”
Section: Controllable Consultation Characteristicsmentioning
confidence: 99%
“…It must be noted however, teacher self-report revealed higher levels of integrity than were shown by direct observation methods (Wickstrom, 1995). For example, in a recent investigation by Wickstrom, Jones, LaFleur, and Witt (1998) the relationship among independent variables and three measures of treatment integrity was explored. Treatment integrity based on teacher self-report was 54%, the use of intervention stimulus products across teachers was 62%, while direct observation of the actual use of interventions revealed that teachers implemented the treatment as intended only 4% of the time (Wickstrom et al, 1998).…”
Section: Assessment Of Treatment Integritymentioning
confidence: 99%